Deep phenotyping of immune cell populations by optimized and standardized flow cytometry analyses. Issue 8 (31st August 2018) - Pitoiset, Fabien; Cassard, Lydie; El Soufi, Karim; Boselli, Lisa; Grivel, Jonathan; Roux, Alexandra; Klatzmann, David; Chaput, Nathalie; Rosenzwajg, Michelle
Abstract: Multicolor flow cytometry is a technology of choice for phenotyping of immune cells, and it can be used routinely for the follow up of patients in clinical trials. But it is challenging to define combinations of conjugated antibodies that efficiently allow the detailed analysis of major immune cell subsets and the identification of rare cell populations. In a collaborative work among the Immunology, Immunopathology, Immunotherapy (I 3 ) laboratory, and the laboratory of immunomonitoring in oncology (L.I.O), we developed and validated 12 different 10‐color flow cytometry panels that allow the deep immunophenotyping of cells from whole blood for the follow up of autoimmune and cancer patients. Here, we describe these optimized flow cytometry panels, showing that they provide the advanced analysis of T cells (including regulatory T cells), B cells, NK cells, MAIT cells, myeloid cells, monocytes, and dendritic cells. Most of the panels have been dried to improve standardization of the labeling and the entire procedure can be performed on less than 2 ml of whole blood. These deep immunophenotyping flow cytometry panels constitute a powerful tool for the monitoring of immune blood cells and will hopefully lead to the discovery of new biomarkers and potential therapeutic targets in autoimmune and cancer clinical trials. © 2018 International Society for Advancement of Cytometry